2012
DOI: 10.1155/2012/405892
|View full text |Cite
|
Sign up to set email alerts
|

Overcoming Barriers in the Management of Hypertension: The Experience of the Cardiovascular Health Program in Chilean Primary Health Care Centers

Abstract: Objective. To assess the blood pressure control and cardiovascular risk factors (CVRFs) in a population of hypertensive patients with access to care under a government-financed program, the Cardiovascular Health Program (CHP). Design. A cross-sectional and multicenter study. Setting. 52 primary care centers, metropolitan area of Santiago, Chile. Participants. 1,194 patients were selected by a systematic random sampling from a universe of 316,654 hypertensive patients. Key Measurements. Demographic information,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
20
5
7

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 19 publications
(37 citation statements)
references
References 23 publications
5
20
5
7
Order By: Relevance
“…In Chile, a 1-year follow-up of the hypertensive population in a government-financed cardiovascular health programme revealed that 91.5% were on antihypertensive drug therapy and BP was controlled in 59.7% of patients, providing further evidence that removing financial barriers is an effective strategy for managing hypertension at the population level. 33 Our findings suggest that policy directed towards reducing the financial barrier to healthcare and medication will likely have a positive impact on the management of hypertension in Ireland.…”
Section: What Is Already Known On This Topicmentioning
confidence: 73%
“…In Chile, a 1-year follow-up of the hypertensive population in a government-financed cardiovascular health programme revealed that 91.5% were on antihypertensive drug therapy and BP was controlled in 59.7% of patients, providing further evidence that removing financial barriers is an effective strategy for managing hypertension at the population level. 33 Our findings suggest that policy directed towards reducing the financial barrier to healthcare and medication will likely have a positive impact on the management of hypertension in Ireland.…”
Section: What Is Already Known On This Topicmentioning
confidence: 73%
“…Algunos de estos factores pudieran, en alguna medida, ser modificados por el manejo integral del paciente hipertenso mediante programas como el PSCV, que explicarían el alto nivel de control de la PA (< de 140/90 mmHg) logrado (47%) en comparación a las cifras publicadas en la Encuesta Nacional 2010 (16,5%) Programas como el PSCV a través de controles periódicos por un equipo multidisciplinario proveen un manejo médico integral y directa o indirectamente, un apoyo emocional importante para el paciente. Estas características han sido descritas anteriormente en programas de manejo similares utilizados en pacientes diabéticos y comentadas por nosotros previamente 36,37 .…”
Section: Discussionunclassified
“…Entre las limitaciones de nuestro estudio está el hecho de que la captación de hombres en el PSCV fue menor que la de las mujeres, lo que hemos comentado en una publicación anterior y que pudiera estar relacionado con conflictos en los horarios de trabajo de los hombres 37 . Otros factores, sugeridos por la menor adherencia que hemos encontrado en los hombres al tratamiento con fármacos antihipertensivos, pudieran estar además en juego.…”
Section: Discussionunclassified
“…5% y adherencia medicamentosa de 37.3 % en hipertensos seguidos por un año en el Programa de Salud Cardiovascular (PSCV) 25 . Este programa del Ministerio de Salud fue iniciado en el año 2002 en los centros de atención primaria con el objetivo de reducir el riesgo de eventos cardiovasculares en los pacientes mas vulnerables (hipertensos y diabéticos) a través de un acceso sin restricciones a programas multidisciplinarios que además del régimen medicamentoso y seguimiento médico perió-dico proveen recomendaciones enfocadas en los hábitos y estilos de vida desfavorables [14][15] . Factores asociados a la predicción de falta de adherencia en los hipertensos seguidos en esta cohorte del PSCV incluyeron bajo nivel educacional y de ingresos económicos, sexo masculino, pobre relación médico-paciente, alto nivel de estrés emocional y depresión [15][16][17][18][19][20][21][22][23][24][25] (Tabla 1).…”
Section: Prevalencia De La Adherencia a La Farmacoterapia Antihiunclassified